2020
DOI: 10.3389/fphar.2019.01671
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Immune-Related Adverse Events Associated With Immune Checkpoint Inhibitor Monotherapy Versus Combination Therapy in Cancer: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Although combination therapy with immune checkpoint inhibitors (ICIs) provides a promising efficacy in multiple cancers, their use is facing challenges for a high incidence of adverse effects. This meta-analysis was conducted to compare the risks of organ-specific immune-related adverse events (IRAEs) associated with ICI monotherapy versus combination therapy among cancer patients.Methods: Electronic databases were systematically searched to include eligible randomized controlled trials (RCTs). Any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…It has been suggested that lung toxicity might be a class effect of anti-PD-1 agents since pneumonitis is more frequent with PD-1 monoclonal antibodies compared to anti-cytotoxic T-lymphocyte-4 (anti-CTL-4) [13] and compared to anti-PD-L1 [31], though the latter is not a uniform finding in all studies [32]. Importantly, it seems that combination immunotherapy (anti-PD-1/PD-L1 in combination with anti-CTL-4) is associated with a higher prevalence of lung toxicity compared to monotherapy [24, 26, 33]. In a recent meta-analysis, the relative risk of pneumonitis was 2.92 (95% CI: 1.60, 5.33; p = 0.0005) in patients who received combination immunotherapy compared to patients who received monotherapy [34].…”
Section: Epidemiologymentioning
confidence: 99%
“…It has been suggested that lung toxicity might be a class effect of anti-PD-1 agents since pneumonitis is more frequent with PD-1 monoclonal antibodies compared to anti-cytotoxic T-lymphocyte-4 (anti-CTL-4) [13] and compared to anti-PD-L1 [31], though the latter is not a uniform finding in all studies [32]. Importantly, it seems that combination immunotherapy (anti-PD-1/PD-L1 in combination with anti-CTL-4) is associated with a higher prevalence of lung toxicity compared to monotherapy [24, 26, 33]. In a recent meta-analysis, the relative risk of pneumonitis was 2.92 (95% CI: 1.60, 5.33; p = 0.0005) in patients who received combination immunotherapy compared to patients who received monotherapy [34].…”
Section: Epidemiologymentioning
confidence: 99%
“…In the series from the city of SĂŁo Paulo, hypothyroidism was frequent (53%), hyperthyroidism was rare, followed by signs of toxicity in the hypothalamic-pituitary-adrenal axis indicated by hypophysitis (16%). However, isolated autoimmune adrenocorticotropic hormone deficiency was identified in five out of 81 patients with endocrine autoimmunity [11][12][13]. Type 1 diabetes was also observed but was uncommon; however, some have reported this disease more frequently.…”
Section: Organ Specific Autoimmunitymentioning
confidence: 99%
“…With nearly 75,000 screen views, the extensive use of the EIOCC IO Toxicity tool provided valuable insights into clinical practice behaviour and learner needs. For instance, a recent meta-analysis of irAEs found that pneumonitis occurred with the lowest prevalence (4.6%) of six toxicities evaluated, including colitis (14.5%) and hepatitis (10.4%) [9]. By comparison, based on the proportion of total screen views, we observed that guidelines for pneumonitis were the second-most frequently accessed (19%), following colitis (22%) and similar to hepatitis (19%); algorithms for arthritis/arthralgia (11%) and rash (11%) were much less commonly accessed.…”
Section: Discussionmentioning
confidence: 99%